2018
DOI: 10.3390/ijms19041194
|View full text |Cite
|
Sign up to set email alerts
|

Separate and Combined Response to UV-B Radiation and Jasmonic Acid on Photosynthesis and Growth Characteristics of Scutellaria baicalensis

Abstract: The negative effects of enhanced ultraviolet-B (UV-B) on plant growth and development have been reported with many species. Considering the ability of jasmonic acid (JA) to improve plant stress tolerance, the hypothesis that JA pretreatment could alleviate the adverse effects of UV-B on S. baicalensis was tested in this study with photosynthesis and growth characteristics. The results showed that UV-B or JA alone both induced photosynthesis inhibition and decreased biomass in stems and leaves. However, the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Upon treatment with a low concentration of MeJA, the photosynthetic and transpiration rate in Huangguogan and Shiranuhi increased significantly, which was consistent with the results in cauliflower (Wu et al 2012). However, when the concentration of MeJA reached 4.4 mM, photosynthesis was significantly inhibited, similar to findings in Baphicacanthus cusia (Lin et al 2019) and S cutellaria baicalensis (Quan et al 2018). In addition, several other studies have shown that the photosynthetic rate of plants is dependent on the concentration of exogenous JAs in a non-linear fashion (Bali et al 2018, Agnihotri andSeth 2020).…”
Section: Role Of Jas In Increasing Photosynthetic Capacity and Chlorosupporting
confidence: 86%
See 1 more Smart Citation
“…Upon treatment with a low concentration of MeJA, the photosynthetic and transpiration rate in Huangguogan and Shiranuhi increased significantly, which was consistent with the results in cauliflower (Wu et al 2012). However, when the concentration of MeJA reached 4.4 mM, photosynthesis was significantly inhibited, similar to findings in Baphicacanthus cusia (Lin et al 2019) and S cutellaria baicalensis (Quan et al 2018). In addition, several other studies have shown that the photosynthetic rate of plants is dependent on the concentration of exogenous JAs in a non-linear fashion (Bali et al 2018, Agnihotri andSeth 2020).…”
Section: Role Of Jas In Increasing Photosynthetic Capacity and Chlorosupporting
confidence: 86%
“…Moreover, a study in Pogostemon cablin (Li et al 2019) demonstrated that extrinsic MeJA can promote the upregulation of photosynthesis‐related proteins. Additional studies have also shown that the use of JAs can impair photosynthetic systems but can enhance the ability of plants to cope with external pressure during stress by increasing photosynthesis (Quan et al 2018, Bali et al 2019). Therefore, the biochemical function of exogenous JAs on photosynthesis is complicated and requires a granular analysis under different concentrations and in various environments.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of JA on photosynthesis have been examined extensively in previous studies, which have yielded mixed results [ 50 ]. While a preponderance of studies support that JA reduces photosynthesis [ 50 , 51 ], there are studies demonstrating that herbivory-induced JA stimulates photosynthesis [ 50 , 52 , 53 ]. Our results support that JA suppresses photosynthesis via downregulation of SBPase, providing additional evidence for JA-induced inhibition of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, external application or genetic engineering to accumulate higher cytokinin content can be a potential strategy to sustain productivity against environmental stress (Bashri et al 2018). Jasmonic acid (JA) is known for its role in defense against various biotic and abiotic stress factors in addition to its growthregulating properties When a plant experiences UV-B stress, JA pre-treatment could counteract its effect by synthesizing anti-oxidative enzymes and protective pigments, which is confirmed in a variety of crops such as wheat, barley and Kentucky bluegrass (Fedina et al 2009;Liu et al 2012;Quan et al 2018).…”
Section: Figure 3 Continuedmentioning
confidence: 99%